The Importance of Frailty in the Assessment of Influenza Vaccine Effectiveness Against Influenza-Related Hospitalization in Elderly People. (26th July 2017) - Andrew, Melissa K; Shinde, Vivek; Ye, Lingyun; Hatchette, Todd; Haguinet, François; Dos Santos, Gael; McElhaney, Janet E; Ambrose, Ardith; Boivin, Guy; Bowie, William; Chit, Ayman; ElSherif, May; et al.
Summary: Frailty has important impacts on influenza vaccine effectiveness (VE). Here, frailty was the most important confounder of VE, and not accounting for frailty underestimated VE. VE was high in nonfrail older adults, but diminished with increasing frailty. Abstract: Background: Influenza is an important cause of morbidity and mortality among older adults. Even so, effectiveness of influenza vaccine for older adults has been reported to be lower than for younger adults, and the impact of frailty on vaccine effectiveness (VE) and outcomes is uncertain. We aimed to study VE against influenza hospitalization in older adults, focusing on the impact of frailty. Methods: We report VE of trivalent influenza vaccine (TIV) in people ≥65 years of age hospitalized during the 2011–2012 influenza season using a multicenter, prospective, test-negative case-control design. A validated frailty index (FI) was used to measure frailty. Results: Three hundred twenty cases and 564 controls (mean age, 80.6 and 78.7 years, respectively) were enrolled. Cases had higher baseline frailty than controls ( P = .006). In the fully adjusted model, VE against influenza hospitalization was 58.0% (95% confidence interval [CI], 34.2%–73.2%). The contribution of frailty was important; adjusting for frailty alone yielded a VE estimate of 58.7% (95% CI, 36.2%–73.2%). VE was 77.6% among nonfrail older adults and declined as frailty increased. Conclusions: Despite commonly held views that VE is poor in older adults, we found that TIV provided good protection against influenza hospitalization in older adults who were not frail, though VE diminished as frailty increased. Clinical Trials Registration: NCT01517191.